Analysis of the theory of planned behavior on the use of halal-labeled cosmetics for students at the University of Islamic Malang - Ma'ruf, Muhammad; Salamah, Nina (Journal of Halal Science and Research, 2023)
The practice of using halal cosmetics involves the intentional involvement of individuals, groups, or organizations in acquiring and using cosmetics that have obtained a halal certification. The behavior of individuals is subject to influence by multiple factors, including attitudes, subjective norms, behavioral control, and intention to use. These factors are motivated by the desires and needs of the individual. This study examines the influence of attitudes, subjective norms, behavioral control, and usage intentions on adopting halal-labeled cosmetics among college students. This research investigates the impact of attitudes, subjective norms, behavioral management, and usage intentions on adopting cosmetics labeled as "halal" among college students. The study employs online surveys as the primary method for data collection. The research utilized a purposive sampling methodology to select a sample size of 110 participants. The present study utilizes a data analysis technique that involves applying multiple regression analysis using the SPSS 25.0 software. The results of this study indicate that the variables of attitude, behavioral control, and intention to use have a statistically significant impact on the utilization of halal-certified cosmetic products. On the other hand, the influence of subjective norms on the utilization of halal decorative goods among students enrolled in the Faculty of Mathematics and Natural Sciences at the University of Islamic Malang is determined to have no significant statistical effect. Keywords: Halal, Cosmetics, Students, Theory of Planned Behavior.